Kontribusi Kemudahan dan Keamanan terhadap Minat Penggunaan Aplikasi BRI Mobile - Lomagio, Afriana; Karim, Rivaldi U. (Al-Buhuts, 2024)
This study aims to determine the magnitude of the influence of convenience (X1) and security (X2) on the Interest in Using (Y) BRI Mobile on Customers of Bank Rakyat Indonesia Unit Kwandang. This study uses a quantitative method with a descriptive research type. The population in this study were Bank Rakyat Indonesia customers who used BRI Mobile (BRImo), totaling 1,453 customers. While the sample used was 94 clients. This study used multiple linear regression analysis with validity, reliability, classical assumption tests, and hypothesis tests. The results of the study showed that convenience had a negative and insignificant effect, and security had a positive and significant effect on interest in use. Simultaneously, convenience and security had a positive effect on customer interest in using BRI Mobile (BRImo).